Apical-out bovine intestinal organoids as an infection model for Cryptosporidium parvum - Mathilde Svensen Varegg; Lucy J. Robertson; Lise Benette Nilsen Hovd; Maria Stokstad; Alejandro Jiménez-Meléndez (Current Research in Parasitology and Vector-Borne Diseases, 2025)
Cryptosporidium parvum is a major pathogen responsible for neonatal calf diarrhoea, but research has been hampered due to the lack of in vitro models that can complete the life cycle. In this scenario, human and murine small intestinal organoids (enteroids) are emerging as new in vitro tools. However, models employing bovine cells, relevant for the pathogenesis in the target species, are lacking. Thus, a panel of bovine enteroids was isolated in this study. Enteroids have an enclosed apical lumen, and the parasite must be delivered to the apical side of the cells to facilitate infection. Two different methods of reversing cell polarity were used to generate bovine apical-out enteroids: dissociation in ethylenediaminetetraacetic acid (EDTA), and dissociation in trypsin. Infection of these enteroids with C. parvum was attempted by incubation of the enteroids with viable, bleach-treated oocysts and subsequent cultivation of the two different enteroid set-ups. Apical-out enteroids dissociated in trypsin supported C. parvum infection and asexual replication, whilst dissociation in EDTA did not. However, only when a high dose of oocysts was administered, were all enteroids included able to support C. parvum replication consistently. When the apical-out enteroids were inoculated with a low dose of oocysts, only one isolate supported C. parvum replication, suggesting enteroid-specific variability. This study reports on infection and asexual replication of C. parvum in bovine apical-out ileal organoids.